Wittgenstein and Psychoanalysis: Telling the Truth about Truth: The Philosopher’s Frame and the Analyst’s Speech - Federico Leoni (EJP import test, 2014)
Summary: In this text, the author comments on Lacan’s statement about the impossibility of “telling the truth about the truth” (Seminar VII), together with Wittgenstein’s idea that we cannot see our eyes seeing (Tractatus logico-philosophicus), nor speak about the language we are speaking. This kind of Urverdrängung (repression) is what both Lacan and Wittgenstein recognize not only as the main obstacle, but also the focal experience, that their practices lead to explore. The author finally shows that the contents, as well as the theatrical structure, of Plato’s dialogues already expose and promote this same experience of incompleteness of the truth; he argues that Lacan’s clinical gesture and Wittgenstein’s idea of das Mystische fully belong to a speculative vein which accompanies and contests, from within and from the very beginning, the history of metaphysics.
Keywords: history of metaphysics; Lacan; metalanguage; Plato; Wittgenstein